South Caucasus and Central Asia - The Belt and Road Initiative : Kyrgyz Republic Country Case Study - World Bank (World Bank, Washington, DC, 2020)
The Kyrgyz economy has been, since its earliest days, the most liberal and open among Central Asian countries resulting in an atypical structural transformation with limited productivity growth. It was the first Central Asian country to become a WTO member in 1998 and its trade share in GDP is the highest in the region. This is largely due to the flourishing cross-border trade with Kyrgyz Republic’s large markets, Dordoi and Kara-Su, intermediating large volumes of goods: importing goods through both formal and informal trade systems, mainly from China, and re-exporting (in few cases with some value-addition) most of that to other economies in the region. It has highly entrepreneurial traders and a logistics-system that caters well to this large ‘entrepot’ trade. Agriculture and light manufacturing have contributed to its exports. This note assesses the potential impact of BRI over connectivity and the Kazakh economy. It looks at how, if fully implemented globally, the BRI is expected to achieve better transport connections and greater economic integration of participating BRI countries, discusses improvements in Kazakhstan’s cross-border transport, electricity and ICT infrastructure to-date, and the potential impact of the completion of BRI transport projects on lowering Kazakh shipment time. It further looks at the likely economic impact of BRI reductions in shipment time on exports, FDI and GDP, the within country regional distribution of that impact and how complementary polices can enhance the positive impact and reduce regional inequity. Finally, it also examines the fiscal risk of scaling-up investment in BRI projects in the coming years without undermining medium-term debt sustainability.